Preserving Arabic Punctuation in the History of Qur'an Writing - Hairuddin Hairuddin (Langkawi: Journal of The Association for Arabic and English, 2020)
This article discusses the preservation of Arabic punctuation in the history of Quran writing using a critical history design. The author begins by recounting the beginning of the laying of Naqth (punctuation), history, type and the form of Naqth (punctuation) found by Abu al-Aswad ad-Duali by giving examples of comparison of classical Qur’an manuscripts not accompanied by punctuation. The author then examines Abu al-Aswad ad-Duali's biography, followed by the reasons for the compiling of Arabic rules and convinces that he was the first person laying down of Arabic rules despite the controversy surrounding it. Likewise, the type of punctuation (the Naqth) discovered is an i’rāb punctuation (the Naqth), not a punctuation of i‘jām.